Effect of methods of routing in QOS in multiservice networks with self-similar load - Кириченко, Людмила Олеговна; Радивилова, Тамара Анатольевна; Кайали, Эйаз (Eastern-European Journal of Enterprise Technologies, 2012)
In this paper we use simulation studied the effect of static and dynamic routing methods on the quality of service in multiservice communication networks with an input self-similar and Poisson traffic